T2-sequence with contrast inversion: diagnostic value in the investigation of gray matter heterotopias - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Hamer, Hajo; Dörfler, Arnd; Engelhorn, Tobias Martin (NeuroReport, 2020)
To compare the diagnostic value of T1-inversion recovery sequence (T1 IR) to that of a T2-sequence with contrast inversion (T2 CI) in the investigation of heterotopias. In this study, we processed a contrast-inverted copy of our coronal T2-sequence of 21 patients with subependymal and subcortical heterotopias on an online picture archiving and communication system workstation. The diagnostic performance of these images was compared with the T1 IR of the same patients by quantitative and qualitative assessments regarding signal-to-noise ratio (SNR), lesion-to-white matter contrast-to-noise ratio (CNR), lesion conspicuity, level of artifacts, overall image quality as well as diagnostic content. SNR values of the T2 CI were significantly higher than those of the T1 IR. CNR values of both sequences were similar. No relevant difference was found for lesion conspicuity and level of artifacts. Overall image quality of the T2 CI was rated slightly better by one reader. Both readers voted the images to have the same diagnostic content. Beside the exact depiction of the hippocampus in the high resoluted T2-sequence, its contrast-inverted copy (T2 CI) is also useful in the detection of heterotopias. In conjunction with the MPRAGE or MP2RAGE as a three-dimensional sequence, it could offer an equivalent and time-saving alternative to the T1 IR in the investigation of this type of malformation of cortical development.
CRIS-Team Scopus Importer:2020-05-29